Draft genome sequence of Solanum aethiopicum provides insights into disease resistance, drought tolerance, and the evolution of the genome - Bo Song; Yue Song; Yuan Fu; Kizito, Elizabeth Balyejusa; Kamenya, Sandra Ndagire; Kabod, Pamela Nahamya; Huan Liu; Muthemba, Samuel; Kariba, Robert; Njuguna, Joyce N.; Maina, Solomon; Stomeo, Francesca; et al. (Oxford University Press, 2019)
The African eggplant (Solanum aethiopicum) is a nutritious traditional vegetable used in many African countries, including Uganda and Nigeria. It is thought to have been domesticated in Africa from its wild relative, Solanum anguivi. S. aethiopicum has been routinely used as a source of disease resistance genes for several Solanaceae crops, including Solanum melongena. A lack of genomic resources has meant that breeding of S. aethiopicum has lagged behind other vegetable crops.